Pertanggungjawaban Hukum Jasa Valet Parking atas Kehilangan Barang Konsumen dalam Perspektif Perlindungan Hukum Perdata - Dewandaru, Rendra Djagad (Fundamental: Jurnal Ilmiah Hukum, 2025)
This study discusses the legal liability of valet parking service providers for the loss of consumers belongings. The research employs a normative juridical method with statutory and conceptual approaches, referring to the Indonesian Civil Code (KUH Perdata) and Law No. 8 of 1999 concerning Consumer Protection. The findings indicate that valet parking agreements are classified as innominate contracts containing elements of both deposit and lease agreements. From the perspective of consumer protection, service providers remain legally responsible for the loss of consumers’ property and cannot exempt themselves through standard clauses. Consumers are entitled to compensation as stipulated in Article 19 of the Consumer Protection Law. This article emphasizes the importance of the service provider’s legal responsibility to ensure safety and legal certainty for consumers.